Intermittent theta burst stimulation (iTBS) and inhibitory control training to reduce binge eating: study protocol for a randomized controlled trial (Be-Nemoic) - Becerra-Losada, Marta; Bernat-Villena, Andrea; Pérez-Comino, Francisco Javier; Algarra-López, Luz Stella; Vilar-López, Raquel; Caracuel, Alfonso (Frontiers in Psychology, 2026)
BackgroundBinge eating is a complex and often underdetected condition characterized by recurrent episodes of excessive food intake accompanied by a perceived loss of control, leading to significant psychological and health consequences. Although pharmacological, psychological, and nutritional treatments are available, their effectiveness remains limited—possibly due to an insufficient understanding of the underlying cognitive and neurobiological mechanisms. Impulsivity, particularly food-specific impulsivity, has been identified as a key factor in binge eating, with inhibitory control deficits associated with increased cravings, maladaptive eating behaviors, and impaired decision-making. Recent studies suggest that inhibitory control training and non-invasive brain stimulation—especially intermittent theta burst stimulation (iTBS) targeting prefrontal regions such as the dorsolateral (dlPFC) or ventromedial prefrontal cortex (vmPFC)—may offer promising therapeutic effects. However, the combined use of cognitive and neuromodulatory interventions has been scarcely investigated. This study aims to determine the efficacy of iTBS combined with inhibitory control training in individuals with binge eating.Methods and analysisIn this double-blind, randomized, controlled trial with parallel groups, 150 individuals with binge eating will be allocated to one of three groups. All participants will undergo inhibitory control training, differing only in the stimulation site: (1) active iTBS of the dlPFC, (2) active iTBS of the vmPFC, or (3) control site vertex stimulation. The interventions will consist of ten sessions over 2 weeks. Primary outcomes will be binge eating symptoms and food craving. Secondary outcomes will include changes in brain activation and connectivity (via fMRI), cognitive functioning, eating behavior, and biological markers. Assessments will be conducted pre-treatment, post-treatment, and at 3-month follow-up. Health service utilization will also be collected to evaluate cost-effectiveness and cost-utility.DiscussionThe results of this study will contribute to the evidence base for combined cognitive and neuromodulatory interventions aimed at improving eating behavior in individuals with binge eating.Trial registrationThe study was registered at http://www.clinicalTrials.gov, number NCT06649994.